PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP TINGKAT KECEMASAN IBU HAMIL DI PUSKESMAS - Made Indah Hermayoni (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Pregnant women who are not psychologically prepared, will experience anxiety during pregnancy and just before the delivery. Anxiety in pregnancy may increase the risk of colic in infants, the delayed motor and mental development of the fetus. The aim of this study was to determine the effect of lavender aromatherapy on the anxiety levels of pregnant women. The study is a pre-experimental research with one group pre-test and post-test design. The total samples of 30 pregnant women were selected by purposive sampling. Data were collected by using the BAI questionnaires before and after the intervention. Intervention was administered for 4 days with lavender aromatherapy. The results obtained before treatment 90% of respondents have mild anxiety, and 10% had a moderate level of anxiety. After treatment 73.3% had mild anxiety and 26.7% did not experience anxiety. The statistical test used was the Wilcoxon Signed Rank Test (p?0,05). The result was p = 0.001, which means there is the effect of lavender aromatherapy on anxiety levels of pregnant women. Based on the research results, it is suggested to the nurses to make use of lavender aromatherapy as an alternative therapy in the treatment of anxiety in pregnant women.